The Influence of Financial Literacy, Religiosity, and Financial Technology on the Financial Behavior of Generation Z in Medan City - Alif Zuan Rahman; Aqwa Naser Daulay; Muhammad Lathief Ilhamy Nasution (Pusat P2M Politeknik Negeri Batam, 2025)
The research intended to examine the influence of financial literacy, fintech, and religiosity on Islamic financial behavior. The phenomenon underlying this research is the low level of public awareness, particularly among the younger generation, regarding financial management based on Sharia principles, despite the increasing trend in the use of Islamic financial products. A quantitative survey method was applied in this research, where data were obtained through questionnaires distributed to respondents and subsequently analyzed using multiple linear regression with SPSS support. The results show that financial literacy, religiosity, and financial technology positively and significantly affect Islamic financial behavior. Among these variables, religiosity has the most dominant influence in encouraging Sharia-compliant financial behavior. The finding suggests that an increased degree of religiosity enhances the likelihood of practicing financial activities in accordance with Islamic teachings. These findings imply that enhancing both religiosity and financial literacy can serve as effective strategies for fostering better Islamic financial behavior within society.